The challenges of engaging women in decisions on the management of breech presentation. (16th November 2010) - Say, RE; Exley, C; Thomson, RG; Robson, SC
Abstract : Background: Engaging women in decisions is a priority for maternity care but remains challenging. The authors investigated the perceived needs of both pregnant women and health professionals to support shared decision making about options for management of breech presentation. Methods: Semistructured interviews with 11 women with breech presentation and 11 health professionals involved in managing breech presentation from two hospitals in NE England. Thematic framework analysis was applied to interview transcripts. Results: There were discrepancies between professionals' and women's views on what might be needed to support decision making. Women described seeking a lot of information from a wide range of different sources and evaluating its quality. In contrast, professionals perceived women would spend limited time considering information and questioned some women's ability to understand and evaluate it. They regarded themselves as being the most appropriate source of information and appeared to be suspicious or dismissive of other sources. Health professionals expressed a preference for external cephalic version (ECV) and described trying to convince women to choose it. In contrast, women had varied attitudes towards ECV. Women who wanted vaginal birth perceived it as a method of enabling 'natural birth' and avoiding Caesarean section. Others saw ECV as frightening, risky and unnatural. Some women preferred elective Caesarean section as a primary choice, which they perceived as offering control, convenience and comfort. Discussion: There is a mismatch between professionals' and women's preferences for information and interventions; in this context shared decision making may benefit from high quality risk communication and decision support.